Impact of Ownership Structure and Corporate Governance on Performance of Nepalese Commercial Banks - G.C., Bishal; Magar, Bikash Thapa; Shah, Brij Bihari; Pant, Dikshya; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2025)
The study examines the effect of ownership structure and corporate governance on performance of Nepalese commercial banks. The dependent variables selected for the study are return on assets and return on equity. The selected independent variables are board size, gender diversity, audit committee size, institutional ownership, foreign ownership and government ownership. The study is based on secondary data of 12 commercial banks with 108 observations for the study period from 2014/15 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of ownership structure and corporate governance on performance of Nepalese commercial banks. The study showed that board size has a positive effect on return on assets and return on equity. It means that larger the board size, higher would be the return on assets and return on equity. Similarly, gender diversity has a positive effect on return on assets. It means that increase in proportion female directors on board leads to increase in return on assets. The results of the study also shows that audit committee has a positive effect on return on assets and return on equity. It implies that larger the size of audit committee, higher would be the return on assets and return on equity. However, foreign ownership has a positive effect on return on assets and return on equity. It implies that higher proportion of foreign ownership leads to increase in return on assets and return on equity. Similarly, government ownership has a positive effect on return on assets and return on equity. It implies that higher proportion of government ownership leads to increase in return on assets and return on equity.